Note—Erratum: A Computational Error in a Nonlinear Programming Example - Clements, Denis T.; Buoni, Frederick B.; Goicoechea, Ambrose (Management Science, 1986)
In an early paper, Griffith and Stewart (Griffith, R. E., R. A. Stewart. 1961. A nonlinear programming technique for the optimization of continuous processing systems. Management Sci. 7 379–392.) presented a method for applying linear programming to a linearized form of some nonlinear programming problems. An arithmetic error in the numerical example given in that paper is discussed, and corrected values of the example are presented.